72 Angiogenesis in response to upregulated hypoxic signalling is dependent on haemodynamic flow. (9th June 2011) - Watson, O J; van Eeden, F J; Gray, C; Chico, T J A
Abstract : Introduction: Hypoxia drives angiogenesis in a range of pathologies. Mutations in von hippel lindau protein (vhl) lead to excessive angiogenesis via upregulation of hypoxic signalling, due to impaired HIF-1α degradation. Physical forces exerted by blood flow have been shown to contribute to vascular remodelling. We therefore used vhl mutant zebrafish to observe the interplay between hypoxic signalling, haemodynamic flow and vascular development. Since NO has been shown to be both pro-angiogenic and released in response to haemodynamic force, we assessed whether NO contributed to angiogenesis in this model. Methods: Vhl mutant zebrafish were crossed with a fli1; GFP transgenic that expresses Green Fluorescent Protein (GFP) in the endothelium. Embryonic vascular development was observed in mutants and wild type siblings by confocal microscopy. To determine the role of blood flow in the angiogenic response, cardiac troponin t2 was knocked down by morpholino antisense injection. To assess the contribution of nitric oxide, embryos were treated with either L-NAME (nitric oxide synthase inhibitor) (1mM) or sodium nitroprusside (NO donor) (100μM) from 24-h post fertilisation (hpf) until imaging at 4dpf. Results: Imaging of the developing trunk vasculature revealed that vhl mutant embryos display excessive and aberrant angiogenesis from 3dpf (Abstract 72 figure 1A, B ). Cardiac troponin T2 knockdown prevented any cardiac contraction, but embryos develop normally due to passive oxygen diffusion. Loss of blood flow did not alter normal intersegmental vessel patterning in either controls (Abstract 72 figure 1C ) or vhl mutants (Abstract 72 figure 1D ). However, loss of blood flow completely prevented excessive angiogenesis in vhl mutants (Abstract 72 figures 1D and 2 ), implying that both blood flow and hypoxic signalling are required for "pathological" angiogenesis but not developmental angiogenesis (vasculogenesis). NO synthase inhibition with L-NAME had no effect, suggesting that the contribution of flow to excessive angiogenesis in response to upregulated hypoxic signalling is NO independent. Conclusion: Angiogenesis in response to hypoxic signalling is critically dependent upon haemodynamic force, compared with developmental vasculogenesis that can proceed in the absence of any blood flow. This indicates a different mechanism of development for hypoxia driven angiogenesis and vasculogenesis which may have important therapeutic implications.